2014
DOI: 10.1590/0074-0276140119
|View full text |Cite
|
Sign up to set email alerts
|

Culture of mouse peritoneal macrophages with mouse serum induces lipid bodies that associate with the parasitophorous vacuole and decrease their microbicidal capacity against Toxoplasma gondii

Abstract: Lipid bodies [lipid droplets (LBs)] are lipid-rich organelles involved in lipid metabolism, signalling and inflammation. Recent findings suggest a role for LBs in host response to infection; however, the potential functions of this organelle in Toxoplasma gondii infection and how it alters macrophage microbicidal capacity during infection are not well understood. Here, we investigated the role of host LBs in T. gondii infection in mouse peritoneal macrophages in vitro. Macrophages cultured with mouse serum (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…[25, 26]. To determine if a similar effect occurs in other cell types, human fibroblasts (HFF) and epithelial cells (HeLa) were infected in vitro with Toxoplasma , and LD biogenesis was monitored throughout infection.…”
Section: Resultsmentioning
confidence: 99%
“…[25, 26]. To determine if a similar effect occurs in other cell types, human fibroblasts (HFF) and epithelial cells (HeLa) were infected in vitro with Toxoplasma , and LD biogenesis was monitored throughout infection.…”
Section: Resultsmentioning
confidence: 99%
“…The peritoneal cells, mainly macrophages and lymphocytes that could provide the cell factor for clone formation, were rapidly depleted within 1 week under culture conditions, because they could not proliferate in vitro without the specific factors. 44,45 To exclude liver fibroblast contamination, the main cell markers of liver fibroblasts (CD34, CD90, AFP, and ALB) for cells isolated with the CSP and MACS methods were investigated by flow cytometry. The results showed that they all expressed below 5% (Fig.…”
Section: Isolation and Characterization Of Hflscsmentioning
confidence: 99%
“…Furthermore, LDs are also involved in inflammatory and infectious diseases . The participation of LDs in infectious disease pathogenesis has been reported for all classes of pathogens, such as viruses, bacteria, fungi, and protozoa, suggesting that LDs participate in the innate and adaptative host immune response to infection. Host LDs may also be exploit as part of the adaptation of pathogens to escape the immune system and as an energy source for intracellular pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Furthermore, LDs are also involved in inflammatory and infectious diseases. 23 The participation of LDs in infectious disease pathogenesis has been reported for all classes of pathogens, such as viruses, 24,25 bacteria, 26,27 fungi, 28 and protozoa, 29,30 suggesting that…”
mentioning
confidence: 99%